2012
DOI: 10.1353/rhe.2012.0007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Undergraduate Debt on the Graduate School Enrollment of STEM Baccalaureates

Abstract: While student loans provide college opportunity for many, undergraduate student debt resulting from typical and heavy borrowing hinders future investments in human capital. Propensity score matching analysis of the NSF’s 2003 National Survey of Recent College Graduates demonstrates that debt negatively affects the graduate school enrollment of bachelor’s degree holders in STEM fields, where debt is measured by a student’s cumulative undergraduate debt relative to the mean debt of his or her baccalaureate gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 66 publications
4
78
0
2
Order By: Relevance
“…Ekstrom, Goertz, Pollack, and Rock (1991) and Fox (1992) both found that undergraduate debt had little effect on students' application to graduate school. However, others (Baum & Schwartz, 1988;Malcom & Dowd, 2012;Millet, 2003) found that undergraduate debt was a factor in students' decision to apply. More recently, Millet (2003) found that undergraduate financial debt was a major predictor of applying to graduate or first professional school.…”
Section: Family Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekstrom, Goertz, Pollack, and Rock (1991) and Fox (1992) both found that undergraduate debt had little effect on students' application to graduate school. However, others (Baum & Schwartz, 1988;Malcom & Dowd, 2012;Millet, 2003) found that undergraduate debt was a factor in students' decision to apply. More recently, Millet (2003) found that undergraduate financial debt was a major predictor of applying to graduate or first professional school.…”
Section: Family Statusmentioning
confidence: 99%
“…For example, students with a debt of $15,000 or more were 1.3 times less likely to apply to post-baccalaureate education compared to students without debt, controlling for a range of other factors. Evaluating how debt may influence graduate school enrollment by race, Malcom and Dowd (2012) found that debt had a negative effect on graduate school enrollment for each racial/ethnic group. The authors concluded that "the amount of borrowing that is 'just right' is no debt at all" (Malcom & Dowd, 2012, p. 292).…”
Section: Family Statusmentioning
confidence: 99%
“…The research also tends to focus on specific MSI categories (HBCU, HSI, or AANAPISI) and not a combination of these types [14][15][16][17][18][19]. MSI completion research has increasingly emphasized the role of STEM education and completion [20][21][22].…”
Section: Traditional Measures Of Student Successmentioning
confidence: 99%
“…Students of different race/ethnicity backgrounds tend to differ in borrowing behaviors. On the undergraduate level, research findings show general aversion of borrowing for Asian students and the opposite as well as higher risk of default and difficulty in repaying student debt for Black students (Addo, Houle, & Simon, 2016;Baum & Steele, 2010;Huelsman, 2015;Jackson & Reynolds, 2013;Malcom & Dowd, 2012;Price, 2004). Hispanic students are more likely to have excessive student debt a few years after graduation than White students (Price, 2004), suggesting difficulty in repaying student debt.…”
Section: Racial Disparities In Student Borrowingmentioning
confidence: 98%